Patient safety management from the perspective of nurses - Lucilena Françolin; Carmen Silvia Gabriel; Andrea Bernardes; Ana Elisa Bauer de Camargo Silva; Maria de Fatima Paiva Brito; Juliana Pereira Machado (SciELO, 2015)
OBJECTIVE To evaluate the actions of patient safety management developed in hospitals, from the perspective of nurses. METHOD This is a cross-sectional, descriptive study of the survey type. Participants were seven hospitals, in which seven nurse managers and 49 sector coordinator nurses (n = 56) answered the instrument prepared by the author. RESULTS The results showed that 100% of hospitals have an adverse event reporting system, 71.4% have a Risk Management Committee and 80% have discussions about the events. There is agreement that these discussions lead to favorable changes for patient safety in the surveyed institutions. The employees' fear of punishment for their faults, and the underreporting of events were the aspects of greatest weakness found. CONCLUSION The institutions should develop organizational policies focused on stimulating event notification and on the implementation of measures directed to a non-punitive organizational culture.